Dialogical and monological functions of the discourse marker bueno in spoken and written Spanish - Posio Pekka; Rosemeyer Malte (Linguistics, 2025)
The Spanish discourse marker bueno has multiple functions ranging from the expression of (dis)agreement to topic management. The present paper sets out to explore what happens when bueno starts to be used in written monological contexts. We examine the use of bueno in spoken sociolinguistic interviews and written internet texts in Mexican and Peninsular Spanish. We propose a unified account of the different functions of bueno based on preference structure and mitigation, tracing a grammaticalization path from adjectival to dialogical and, subsequently, monological uses of bueno. We use regression analysis to examine the hypotheses that (a) written medium serves as a catalyst for monologization, and (b) the two dialects studied represent two different stages of grammaticalization of bueno. While the first hypothesis is confirmed, evidence supporting the second hypothesis is less conclusive, suggesting that written uses are more similar between the two dialects than the spoken ones.